PROFESSOR ORLANDO FALS BORDA, HIS IDEAS SOCIAL AND EDUCATIONAL IDEAS FOR THE COLOMBIAN SOCIETY CHANGE (2011)
This research work of HISULA, in the series of Latin American Educators, intends to study Professor Orlando Fals Borda’s educational ideas as well as the action-research scientific methodology developed by him, one of the most outstanding ideologists of the university education in Colombia. Special emphasis is given on the analysis of his most known works related to a sociological study of the Andean peasants and the Man and the Earth in the Cundi-boyacense region at the Andean Highland. Born in Barranquilla, this illustrious educator had particular interest in developing Colombian people’s sociological research and defending the education role in the social change. With his Action-Research methodology, he pointed out the Colombian education direction, in which students become their own learning protagonists through “learning by doing” philosophy. He trained a generation of noticeable sociologists, devoted to social research in a critical time of changes. Most of his work was carried out at the Sociology Faculty of Universidad National. It is to stand out his methodology of “Participatory Action-Research”. His ideology influence was definitive and undeniable for the Constitución Nacional of 1991, which clearly kept in it some of his ideas.